The strategy of nanomaterials in polymeric membranes for water treatment: Nanocomposite membranes / La estrategia de los nanomateriales en membranas poliméricas para el tratamiento de agua: membranas nanocompuestas - Roberto Castro-Muñoz (Tecnología y ciencias del agua, 2020)
Membrane-based technologies, such as micro (MF), ultra (UF) and nanofiltration (NF), have been widely applied for water treatment applications; however, the limitations of pure polymeric membranes have encouraged the incorporation of inorganic nanomaterials to enhance their performance. Today, nanocomposite membranes have greatly increased the attention of researchers for different water treatment applications, e.g., water purification, wastewater treatment, removal of microorganisms, chemical compounds and heavy metals. To date, different types of nanomaterials have been incorporated into polymeric membranes, such as carbon nanotubes (CNT), zinc oxide (ZnO), graphene oxide (GO), titanium dioxide (TiO2), Ag and Cu-based nanoparticles, to mention just a few. Thereby, the aim of this paper is to show a brief overview about the effect on embedding these materials into polymeric membranes according to the recent literature inputs in the field of water treatment.